Iberian dry-cured ham as a potential source of α-glucosidase-inhibitory peptides. (April 2020) - Mora, Leticia; González-Rogel, Diego; Heres, Alejandro; Toldrá, Fidel
Graphical abstract: Highlights: α-Glucosidase inhibitory peptides are generated in Iberian dry-cured ham. A total of 63 sequences of peptides were identified in most active fractions. The multifunctionality of α-glucosidase inhibitory peptides was confirmed. Abstract: Iberian dry-cured ham is a meat product known as a source of different bioactive peptides due to its high protein content and intense hydrolysis during its processing. In this study, the potential of α-glucosidase inhibitory peptides generated in Iberian dry-cured ham was evaluated for the first time. After size-exclusion chromatography and high-performance liquid chromatography using different stationary phases, the characterization and identification of the peptide sequences contained in the most active fractions was done using MALDI-ToF mass spectrometry and Q-ToF mass spectrometry in tandem. A total of 16 and 47 sequences of peptides were identified in the two most active fractions. On the other hand, the α-glucosidase inhibitory activity of previously identified bioactive peptides in Spanish dry-cured ham such as AEEEYPDL and LGVGG was established, confirming their multifunctionality.